Green Consumer Behavior of Women in Purchasing Local Environmentally Friendly Detergent Products - Viola De Yusa; Riyadini Riyan Utami (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes how environmental knowledge and attitudes affect women's green consumer behavior when purchasing eco-friendly detergent. Methodology: This study uses a type of causality research, and sampling in this study uses a non-probability sampling method using an incidental sampling technique with 120 sample respondents. The method used in this study was multiple linear regression analysis. Results: The results of the study showed that environmental knowledge positively affected green consumer behavior in women purchasing environmentally friendly detergent products. This is because women are more concerned about environmental issues and understand the impact of environmental pollution, and women who are active in recycling activities are more likely to choose and buy environmentally friendly products. Conclusions: This study significantly enhances our understanding of the factors influencing environmentally conscious consumer behavior, particularly among women, when selecting eco-friendly detergent products. The findings suggest that knowledge of recycling, along with related attitudes and behaviors, plays a crucial role in shaping women's preferences for more sustainable products. Limitations: The focus of this study is only on female consumers; therefore, it does not examine how male consumers buy environmentally friendly detergents. The study cannot be generalized to a wider population because the respondents were limited to certain areas. Contributions: Testing the relevance of consumer behavior theories, such as the Theory of Planned Behavior (TPB), to eco-friendly detergent purchases provides valuable insights for local manufacturers to design effective marketing strategies targeting environmentally conscious female consumers.